Neuralgia Pasca Herpes - Hafiza Qaristy; Wizar Putri Melaratna (Jurnal Medika Nusantara, 2024)
Herpes zoster, also known as snake pox and shingles , is a skin disease caused by reactivation of latent varicella zoster virus (VVZ) infection also known as human herpesvirus-3 (HHV-3) in the dorsal root sensory ganglion after primary infection. Mrs. A, 64 years old female was consulted with complaints of burning pain in the lower right abdomen to the right waist, that happened approximately 2 month after diagnosed with herpes zoster. Based on anamneses and physical examination the patient was diagnosed by Postherpetic neuralgia. Postherpetic neuralgia is persistent chronic pain and the most common complication in herpes zoster. In the majority of patients, pain from shingles is usually felt within 2 to 4 weeks. However, patients who experience NPH will experience continuous pain at the site of infection for 3 to 9 weeks after infection. The patients was given supportive treatment accompanied by education that can be provided to relieve the symptoms caused by this disease.